The impact of pre-procedure heart rate on adverse clinical outcomes in patients undergoing percutaneous coronary intervention: Results from a 2-year follow-up of the GLOBAL LEADERS trial. (June 2020) - Wang, Rutao; Takahashi, Kuniaki; Chichareon, Ply; Gao, Chao; Kogame, Norihiro; Modolo, Rodrigo; Tomaniak, Mariusz; Kawashima, Hideyuki; Ono, Masafumi; Hara, Hironori; Schächinger, Volker; Tonev, Gincho; et al.
Abstract: Background and aims: The prognostic impact of pre-procedure heart rate (PHR) following percutaneous coronary intervention (PCI) has not yet been fully investigated. This post-hoc analysis sought to assess the impact of PHR on medium-term outcomes among patients having PCI, who were enrolled in the "all-comers" GLOBAL LEADERS trial. Methods and results: The primary endpoint (composite of all-cause death or new Q-wave myocardial infarction [MI]) and key secondary safety endpoint (bleeding according to Bleeding Academic Research Consortium [BARC] type 3 or 5) were assessed at 2 years. PHR was available in 15, 855 patients, and when evaluated as a continuous variable (5 bpm increase) and following adjustment using multivariate Cox regression, it significantly correlated with the primary endpoint (hazard ratio [HR] 1.06, 95% confidence interval [CI] 1.03–1.09, p  < 0.001). Using dichotomous cut-off criteria, a PHR>67 bpm was associated with increased all-cause mortality (HR 1.38, 95%CI 1.13–1.69, p  = 0.002) and more frequent new Q-wave MI (HR 1.41, 95%CI 1.02–1.93, p  = 0.037). No significant association was found between PHR and BARC 3 or 5 bleeding (HR 1.04, 95% CI 0.99–1.09, p  = 0.099). There was no interaction with the primary ( p -inter = 0.236) or secondary endpoint ( p -inter = 0.154) when high and low PHR was analyzed according to different antiplatelet strategies. Conclusions: Elevated PHR was an independent predictor of all-cause mortality at 2 years following PCI in the "all-comer" GLOBAL LEADERS trial. The prognostic value of increased PHR on outcomes was not affected by the different antiplatelet strategies in this trial. Graphical abstract: Image 1 Highlights: Elevated pre-procedure heart rate was an independent predictor of all-cause mortality at 2 years following percutaneous coronary intervention (PCI). Elevated pre-procedure heart rate did not impact the bleeding events at 2 years following PCI. Ticagrelor monotherapy versus standard dual antiplatelet therapy did not improve the bad ischemic prognosis of high pre-procedure heart rate.